Comparison between mitral valve repair and replacement in active infective endocarditis - Thitipong Tepsuwan (2019)
© 2019, The Japanese Association for Thoracic Surgery. Background: Mitral valve repair has been proved to provide better outcomes when compared with replacement in degenerative disease. However, it is still unclear that benefits of repair still remain in active endocarditis. Patient clinical conditions and severity of tissue destruction might limit successful durable repair. Methods: Of all 247 patients who received surgery during active phase of native left-sided endocarditis from Jan 2006 to Dec 2017, 114 had mitral valve procedures due to active infection of mitral valve apparatus (38 repair and 76 replacement). Perioperative data and mid-term outcomes were retrospectively compared. Results: Mean age was 46.4 years old. Repair group had significantly less patients with NYHA class IV (18.4% vs 56.6%, p = 0.001). Both groups had preserved ejection fraction but accompanied by severe pulmonary hypertension. Major organism was streptococci (50%) and timing of surgery was 11 days after diagnosis. Bypass and cross-clamp time were similar but repair group had significantly less combined procedures. Bi-leaflet involvement was common (47.4% vs 57.6%) and valve lesions were comparable. There was 13.2% of postoperative moderate to severe mitral regurgitation in repair group without recurrent endocarditis. Repair group tended to have better 5-year survival estimates (91.6% vs 70.0%, p = 0.08) with comparable reoperation rate (7.9% vs 2.6%). By logistic regression analysis, mitral valve replacement was more likely to be performed in patients with decompensated heart failure and combined procedures. Conclusions: Mitral valve repair during active endocarditis can be safely performed with good mid-term outcomes, especially in selected group of patients without extremely high surgical risk.